NOAA Satellite Weather Stations: State of the Art, Perspective and Future Projection - Julián Peña-Becerra; Edith Paola Estupiñán-Cuesta; Juan Carlos Martínez-Quintero (Visión Electrónica, 2021)
This document presents a documentary review of the impact done by ground satellite stations linked to NOAA's meteorological satellites, highlighting the implementation of software defined radio and some possible applications that could be given to satellite stations in terms of data and information processing. This work is done in order to find the main characteristics of these satellite communications systems and several applications, which are oriented towards the monitoring of natural phenomena for documentation and prevention; presenting the projection with the implementation is in Cloud and research through years.